2023
DOI: 10.1038/s41467-023-38230-0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide exchange is sufficient for Hsp90 functions in vivo

Abstract: Hsp90 is an essential eukaryotic chaperone that regulates the activity of many client proteins. Current models of Hsp90 function, which include many conformational rearrangements, specify a requirement of ATP hydrolysis. Here we confirm earlier findings that the Hsp82-E33A mutant, which binds ATP but does not hydrolyze it, supports viability of S. cerevisiae, although it displays conditional phenotypes. We find binding of ATP to Hsp82-E33A induces the conformational dynamics needed for Hsp90 function. Hsp90 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…Thus, conformational changes are thermally driven and not fuelled by ATP turnover. A recent study suggests that it is not the hydrolysis of ATP but the repositioning of its gamma phosphate which is sufficient for Hsp90 function 19 . They emphasize that returning to the open, ADP-bound state is essential, which can occur either by nucleotide exchange (non-directional) or by hydrolysis (directional).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, conformational changes are thermally driven and not fuelled by ATP turnover. A recent study suggests that it is not the hydrolysis of ATP but the repositioning of its gamma phosphate which is sufficient for Hsp90 function 19 . They emphasize that returning to the open, ADP-bound state is essential, which can occur either by nucleotide exchange (non-directional) or by hydrolysis (directional).…”
Section: Discussionmentioning
confidence: 99%
“…This would allow first for the formation of a functional complex and then, e.g. after ATP hydrolysis or nucleotide exchange 19 , for recycling of all components. We speculate that this is the long searched-for function of Hsp90’s ATPase function, namely to disassemble a functional complex after the job is done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1B , most of the differences between the two isoforms are located in the amino-terminal domain, which is likely the basis for differences in ATPase activity and sensitivity to Hsp90 inhibitors that bind the nucleotide-binding pocket ( Girstmair et al, 2019 ). Early studies showed that ATP hydrolysis was also essential in yeast, but subsequent studies suggest that nucleotide exchange, rather than hydrolysis, is sufficient for viability ( Zierer et al, 2016 ; Reidy et al, 2023 ). Additional structural studies, coupled with functional analysis in yeast, identified residues within a flexible loop of the middle domain that play an important role regulating ATP hydrolysis ( Meyer et al, 2003 ).…”
Section: Hsp90 Structure and The Conformational Cyclementioning
confidence: 99%
“…Upon ATPhydrolysis, the complex opens again and releases the maturated kinase as well as the cochaperone, leaving Hsp90 ready for yet another cycle (Verba and Agard 2017;Eckl et al 2015;Keramisanou et al 2022;Schopf et al 2017). Alternatively, it was shown that Hsp90 does not close upon ATP binding itself (Lopez et al 2021), but instead (Reidy et al 2023) proposed recently that its conformational changes are triggered by the proper positioning of ATP's gamma phosphate. Furthermore, it was proposed that the cycle might also be linked to dephosphorylation of a kinase (Jaime-Garza et al 2023).…”
Section: Introductionmentioning
confidence: 99%